Vplyv inhibície HSP90 na viabilitu a bunkový cyklus v závislosti od stavu p53 - Pastorek, M; Müller, P; Vojtěšek, B (Klinicka onkologie, 2016)
BACKGROUND: Chaperone system inhibition is a recent promising strategy for cancer treatment that exploits increased metabolic needs required for rapid proliferation as well as higher level of proteotoxic stress in neoplastic cells. Chaperone HSP90 plays a key role in proper folding of many de novo synthesized proteins, so-called clients, including tumor suppressor p53 which is commonly mutated in majority of cancers. Aim of this work was therefore to understand the impact of HSP90 inhibition by NVP-AUY922 on breast cancer cell lines with wild-type and mutated p53. METHODS: Flow cytometry was used to analyze cell viability by fluorescein diacetate assay and changes in cell cycle. Western blotting was used to analyze expression of p53 and p21 proteins. RESULTS: Analysis of cell viability after HSP90 inhibition revealed higher sensitivity of cell line with wild-type p53. Cell cycle analysis then showed that both cell lines undergo increase in G2/M block of the cell cycle, but wild-type cell line had also substantial decrease in proliferative capacity of treated cells. We also observed increased expression of negative cell cycle regulator p21 in cell line with wild-type p53. CONCLUSIONS: Since p21 is directly regulated by p53, our results suggest that mutation status of p53 can be important factor in treatment of breast cancer cells by HSP90 chaperone inhibition and that wild-type p53 can increase sensitivity to HSP90 inhibition.Key words: breast cancer - cell cycle - chaperone - HSP90 - TP53 - p21 - p53 - NVP-AUY922This work was supported by the project MEYS - NPS I - LO1413.The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 6. 5. 2016Accepted: 17. 5. 2016.
Keywords: nádorový supresorový protein p53; nádorové buněčné linie; Breast Neoplasms; Cyclin-Dependent Kinase Inhibitor p21; isoxazoly; mutace; Isoxazoles; Cell Proliferation; Cell Line, Tumor; Tumor Suppressor Protein p53; Antineoplastic Agents; kontrolní body M fáze buněčného cyklu; proteiny tepelného šoku HSP90; kontrolní body fáze G2 buněčného cyklu; protinádorové látky; Mutation; Humans; inhibitor p21 cyklin-dependentní kinasy; G2 Phase Cell Cycle Checkpoints; viabilita buněk; Cell Survival; M Phase Cell Cycle Checkpoints; nádory prsu; proliferace buněk; resorcinoly; Resorcinols; lidé; HSP90 Heat-Shock Proteins